'Pic-N-Spell': Promoting the application of knowledge through active learning / Nurma Abdul Manap ... [et al.] - Abdul Manap, Nurma; Bakar, Sulaila; Muslim, Mazni; Md Yusof, Nor Hidayah; Mohamed Hamdan, Hanani (Universiti Teknologi MARA, Pahang, 2021)
Every language educator knows that motivating language learners can be a very difficult task. It is more difficult if the learners are learning a second or third language. Learners are unmotivated because they are not interested in what is being taught in a classroom setting. Based on our experience in handling language programs in SK LKTP Krau (1), a rural school, we have found that the usage of English among the pupils is very minimal. The truth is, the main culprit is the approach being used to present the content. The main reason learners actively participate in their learning process is purely for enjoyment. When they enjoy the process, they participate and finally learn. Pic N Spell is a language game developed to enhance not only the spelling ability of the language learners but also their pronunciation of the words. In order to ensure the effectiveness of the game, pre-test and post-test were conducted, questionnaires were distributed to 35 pupils from year four, five and six. The researchers inspire to bring forth this language game based on their prior experiences interacting with rural school pupils. Pic N Spell is solely developed to spark interest and enjoyment in learning English. Based on the questionnaire it is proven that the pupils enjoyed themselves thoroughly. The data obtained proved that the game has made them learn better in a fun and competitive setting. Such findings indicate that language educators need to find unconventional methods in teaching English to ignite the interest and to minimize language learning anxiety.